Conceptualisation of job-related wellbeing, stress and burnout among healthcare workers in rural Ethiopia: a qualitative study - Medhin Selamu; Graham Thornicroft; Abebaw Fekadu; Charlotte Hanlon (BMC, 2017)
Abstract Background Wellbeing of healthcare workers is important for the effective functioning of health systems. The aim of this study was to explore the conceptualisations of wellbeing, stress and burnout among healthcare workers in primary healthcare settings in rural Ethiopia in order to inform the development of contextually appropriate interventions. Methods A qualitative study was conducted in a rural zone of southern Ethiopia. A total of 52 frontline primary healthcare workers participated in in-depth interviews (n = 18) or Focus Group Discussions (FGDs) (4 groups, total n = 34). There were 35 facility based healthcare professionals and 17 community-based health workers. Data were analysed using thematic analysis. Results Most participants conceptualised wellbeing as absence of stress rather than as a positive state. Many threats to wellbeing were identified. For facility-based workers, the main stressors were inadequate supplies leading to fears of acquiring infection and concerns about performance evaluation. For community health workers, the main stressor was role ambiguity. Workload and economic self-sufficiency were a concern for both groups. Burnout and its symptoms were recognised and reported by most as a problem of other healthcare workers. Derogatory and stigmatising terms, such as "chronics", were used to refer to those who had served for many years and who appeared to have become drained of all compassion. Most participants viewed burnout as inevitable if they continued to work in their current workplace without career progression. Structural and environmental aspects of work emerged as potential targets to improve wellbeing, combined with tackling stigmatising attitudes towards mental health problems. An unmet need for intervention for healthcare workers who develop burnout or emotional difficulties was identified. Conclusion Ethiopian primary healthcare workers commonly face job-related stress and experience features of burnout, which may contribute to the high turnover of staff and dissatisfaction of both patients and providers. Recent initiatives to integrate mental healthcare into primary care provide an opportunity to promote the wellbeing of healthcare workers and intervene to address burnout and emotional problems by creating a better understanding of mental health.